2015
DOI: 10.1039/c5cp01735a
|View full text |Cite
|
Sign up to set email alerts
|

Endeavour to simplify the frustrated concept of protein-ammonium family ionic liquid interactions

Abstract: The large amount of attention earned by ionic liquids (ILs) in the various physical and chemical sciences has been attributed to their unique, designer nature. In the past few years, the role of ILs in protein folding/unfolding has been rapidly growing. In light of the increasing importance of ILs, it is desirable to systematize the ion effects on protein properties such as structure stability, activity and enantioselectivity. Various studies available in the literature show ILs as a potential solvent medium f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 140 publications
(319 reference statements)
1
44
0
Order By: Relevance
“…[19][20][21][22][23] Studies have shown ammonium-based ILs to act as better stabilizing agent for proteins as compared to imidazolium-based ILs. 24 Our research group has out carried protein stability studies in both ammonium and imidazolium-based ILs. 16,[25][26][27][28][29] Recently, Jha et al 27 showed the destabilization of Mb and Hb in ammonium-based ILs which was much unexpected result because of the fact that ammonium-based ILs are known as good protein stabilizers.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] Studies have shown ammonium-based ILs to act as better stabilizing agent for proteins as compared to imidazolium-based ILs. 24 Our research group has out carried protein stability studies in both ammonium and imidazolium-based ILs. 16,[25][26][27][28][29] Recently, Jha et al 27 showed the destabilization of Mb and Hb in ammonium-based ILs which was much unexpected result because of the fact that ammonium-based ILs are known as good protein stabilizers.…”
Section: Introductionmentioning
confidence: 99%
“…These unique properties of ILs make them very attractive nonaqueous solvents for protein stability studies. It is revealed from various studies that physicochemical properties of ILs can play a pivotal role in altering the structure, stability and activity of proteins/enzymes [44]. Moreover, ILs offer new possibilities of application of solvent engineering to enzymatic reactions.…”
Section: Protein Stability In the Presence Of Ilsmentioning
confidence: 99%
“…Studies carried out by various groups using CT suggest that the physical properties of ILs such as polarity and hydrophobicity play a major role in their stabilizing behavior toward CT [18,52,53]. Among various families of ILs, ammonium-based ILs are identified to display their wide range application in biochemical processes [44].…”
Section: Protein Stability In the Presence Of Ilsmentioning
confidence: 99%
See 2 more Smart Citations